2020
DOI: 10.1007/s40211-020-00380-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of fibroblast growth factor 21 with alcohol consumption and alcohol liver cirrhosis

Abstract: Summary Background Fibroblast growth factor 21 (FGF21) is produced in the liver and binds to different complex receptor/coreceptor systems. Besides many other processes, FGF21 regulates the intake of simple sugars and alcohol. Increased levels of FGF21 decrease harmful alcohol intake in mice. To increase our understanding on the relationship between FGF21 and alcohol intake in humans, we aimed to measure FGF21 levels in patients with alcoholic liver cirrhosis (ALC) in comparison to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Endogenous FGF21 and pharmacologic administration of FGF21 suppress alcohol consumption in rodents and non-human primates Both chronic alcohol consumption and acute binge-like consumption increase circulating levels of endogenous FGF21 (Desai et al, 2017;Liu et al, 2016;Søberg et al, 2018;Wagner-Skacel et al, 2021). To determine if circulating FGF21 induced by ethanol consumption is derived from the liver, as is the case for many nutritional challenges (Flippo and Potthoff, 2021), we deleted FGF21 in the liver by administering AAV viruses expressing either Cre recombinase or a control construct under a liver-specific promoter (AAV-TBG-Cre and AAV-TBG-Con, respectively) to mice harboring a floxed FGF21 allele (FGF21 fl/fl ) (Figures S1A and S1B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Endogenous FGF21 and pharmacologic administration of FGF21 suppress alcohol consumption in rodents and non-human primates Both chronic alcohol consumption and acute binge-like consumption increase circulating levels of endogenous FGF21 (Desai et al, 2017;Liu et al, 2016;Søberg et al, 2018;Wagner-Skacel et al, 2021). To determine if circulating FGF21 induced by ethanol consumption is derived from the liver, as is the case for many nutritional challenges (Flippo and Potthoff, 2021), we deleted FGF21 in the liver by administering AAV viruses expressing either Cre recombinase or a control construct under a liver-specific promoter (AAV-TBG-Cre and AAV-TBG-Con, respectively) to mice harboring a floxed FGF21 allele (FGF21 fl/fl ) (Figures S1A and S1B).…”
Section: Resultsmentioning
confidence: 99%
“…suppresses alcohol consumption by enhancing the excitability of a specific subpopulation of these neurons. The association of increased FGF21 levels with alcohol consumption and alcohol liver cirrhosis (Wagner-Skacel et al, 2021) may suggest that a pathology in this pathway contributes to alcohol dependency. Importantly, FGF21 and the FGF21 analog PF-05231023 effectively function to decrease alcohol intake even when administered after prolonged ethanol exposure in mice and primates.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Both preclinical and clinical studies recently found that alcohol consumption increases endogenous FGF21 levels. 4 , 5 Albeit preliminary, these findings suggest that elevated FGF21 following alcohol use may lead to reduced alcohol intake, potentially through acting on the co-receptor β-klotho (encoded by the KLB gene) expressed in the brain. 5 Therefore, it is possible to hypothesize that a liver-brain axis pathway like FGF21 may serve as a viable target for AUD treatment.…”
Section: Main Textmentioning
confidence: 88%
“… 4 , 5 Albeit preliminary, these findings suggest that elevated FGF21 following alcohol use may lead to reduced alcohol intake, potentially through acting on the co-receptor β-klotho (encoded by the KLB gene) expressed in the brain. 5 Therefore, it is possible to hypothesize that a liver-brain axis pathway like FGF21 may serve as a viable target for AUD treatment. However, little work to date has investigated neural mechanisms underlying FGF21’s interplay with alcohol consumption as well as its effects in higher order mammals.…”
Section: Main Textmentioning
confidence: 88%
“…Yang et al investigated serum levels of FGF-21 in diagnosing nonalcoholic steatoheaptitis (NASH) and the critical stage of non-alcoholic fatty liver disease (NAFLD) [19]. In a recent study, Wagner-Skacel et al showed that increased FGF21 levels in patients correlated with recent alcohol consumption [20]. Remmler et al indicated that the serum level of IL-6 and Model of End-Stage Liver Disease (MELD) scores are associated with mortality in patients with end-stage liver disease, evaluated for liver transplantation [21].…”
Section: Discussionmentioning
confidence: 99%